Response of onion to different levels of drip irrigation and fertigation in Coastal Plain Zone of Odisha - PRADHAN, P.C.; DALAI, A.; SHARMA, R.P. (Journal of Soil and Water Conservation, 2024)
Field experiments were conducted to assess the response of irrigation and fertigation levels on onion (Allium cepa L.) Cv. Agrifound Light Red during three consecutive rabi seasons from 2016-17 to 2018-19 at research farm of Precision Farming Development Centre, Odisha University of Agriculture and Technology, Bhubaneswar. The experiment was laid out in randomized block design (RBD) with ten treatments and three replicates. Three levels of irrigation@100, 80, 60% of ETc and three levels of fertigation with water soluble fertilizers @ 100, 80, 60% of soil test based recommended dose were applied during experimentation. The results of the study showed that the onion Cv. Agrifound Light Red, when cultivated in sandy loam soil during winter season recorded maximum yield and irrigation water use efficiency of 25.96 t ha-1 and 8.65 kgm-3, respectively for treatment with irrigation at 80%ETc and fertigation at 100% recommended dose of fertilizer (RDF), but was at par with irrigation at 80% of ETc and fertigation at 80% of RDF. Fertiliser use efficiency was observed to have inverse relationship with fertigation levels and maximum value of 132.99 kg was observed per kg of NPK at 80% irrigation and 60% RDF fertigation combinations. Hence, it is recommended to grow winter onion with irrigation at 80% level and fertigation at 80% of RDF for higher yield as well as saving of irrigation water and fertilizers by 20%.